Examining the Challenges of Integrating GeoGebra Software in the Teaching and Learning of Coordinate Geometry in Colleges of Education in the North West Zone of Nigeria - Saidu, Sani; Rabiu, Ahmed Tijjani; Hamzat, Bashirat K (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2024)
This study titled 'The Challenges of Integrating GeoGebra software in the Teaching and Learning of Coordinate Geometry" was carried out with the following objectives: to find out the barriers that prevent the use of GeoGebra in teaching and learning of Coordinate Geometry in Nigerian Colleges of Education;; to find the compatibility of the GeoGebra software with the existing text materials in Nigeria Colleges of Education among others. The work was carried out using four research questions; four hypotheses and a sample of fifty-four (54) Mathematics Lecturers from three Federal Colleges of Education. The instrument of the study was adapted from Agyei and Benning (2015) which has a reliability coefficient of 0.89. The findings revealed that lecturers in Colleges of Education face challenges in using GeoGebra such as time constraints, inadequate equipment, and non-availability of functional internet services among others. It was found that GeoGebra software is compatible with the existing text materials. Moreso, gender difference was not found in the attitude towards GeoGebra among lecturers of Colleges of Education. Finally, it was recommended that NCCE redesign the NCE curriculum in order to allocate more time for each course.